Faces of Béxar : Early San Antonio and Texas - Teja, Jesús F. de la, 1956- (Book collections on Project MUSE., 2016)
Faces of Bexar showcases the finest work of Jesús F. de la Teja, a foremost authority on Spanish colonial Mexico and Texas through the Republic. These essays trace the arc of the author's career over a quarter of a century. A new bibliographic essay on early San Antonio and Texas history rounds out the collection, showing where Tejano history has been, is now, and where it might go in the future. For de la Teja, the Tejano experience in San Antonio is a case study of a community in transition, one moved by forces within and without. From its beginnings as an imperial outpost to becoming the center of another, newer empire--itself in transition--the social, political, and military history of San Antonio was central to Texas history, to say nothing of the larger contexts of Mexican and American history. Faces of Bexar explores this and more, including San Antonio's origins as a military settlement, the community's economic ties to Saltillo, its role in the fight for Mexican independence, and the motivations of Tejanos for joining Anglo Texans in the struggle for independence. Taken together, Faces of Bexar stands to be a milestone in the growing literature on Tejano history.